Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18677/enciclopedia_biosfera_2016_109
|View full text |Cite
|
Sign up to set email alerts
|

Sobrevivência E Crescimento Inicial De Espécies Arbóreas Nativas Na Restauração De Nascentes No Sul De Minas Gerais

Abstract: RESUMOEste estudo teve como objetivo, avaliar a sobrevivência e o crescimento inicial de sete espécies arbóreas nativas na restauração ecológica de florestas ciliares no entorno de nascentes na região Sul de Minas Gerais. As espécies estudadas foram Trema micrantha (Cannabaceae), Guazuma ulmifolia (Malvaceae), Lithraea molleoides (Anacardiaceae), Cedrela fissilis (Meliaceae), Aspidosperma parvifolium (Apocynaceae), Machaerium villosum (Fabaceae) e Handroanthus serratifolius (Bignoniaceae). O experimento foi re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(6 reference statements)
0
2
1
5
Order By: Relevance
“…Regarding the root collar diameter, Sgarbi et al (2012) found a diameter of 3.8 cm for Trema micrantha at six months of age, close to that registered in this study for the same period (dc = 3.31 cm). At 12 months of age the species presented a diameter of 1.33 cm, surpassing that found by Alvarenga et al (2016), which ranged from 0.26 to 0.88 cm at 11 months. However, it remained lower than that found by Nogueira (2015) for the same period (dc = 8.48 cm).…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Regarding the root collar diameter, Sgarbi et al (2012) found a diameter of 3.8 cm for Trema micrantha at six months of age, close to that registered in this study for the same period (dc = 3.31 cm). At 12 months of age the species presented a diameter of 1.33 cm, surpassing that found by Alvarenga et al (2016), which ranged from 0.26 to 0.88 cm at 11 months. However, it remained lower than that found by Nogueira (2015) for the same period (dc = 8.48 cm).…”
Section: Resultscontrasting
confidence: 55%
“…According to these authors, the lowest survival values found for the species are justified due to an exceptional period of flooding in the planted area, resulting from precipitation above the monthly average. The survival found by Alvarenga et al (2016) for Trema micrantha ranged from 40% to 100% at 11 months of age. This variation was attributed to the soil, since the characteristics between the sites were different.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A remoção de vegetação nativa de maneira indiscriminada para a abertura de extensas áreas de agricultura e pastoreio é um dos exemplos de ação antrópica comumente relatada e que tem influenciado o aumento de áreas degradadas (VENTUROLI et al, 2013). Em vista da degradação dos ecossistemas, esforços têm sido realizados no intuito de restaurar os ambientes e garantir os recursos essenciais à vida (ALVARENGA et al, 2016).…”
Section: Introductionunclassified
“…Devido ao manejo inadequado do uso do solo, seja por impudência ou desinformação da legislação vigente, algumas APPs das nascentes têm sido degradadas, diminuindo a capacidade de infiltração de água no solo e desequilibrando a sustentabilidade desses ecossistemas, podendo ocasionar até a seca dessas nascentes (ALVARENGA et al, 2016).…”
Section: Introductionunclassified